Managing Ethical Dilemmas in Community-Based Participatory Research With Vulnerable Populations. Issue 4 (July 2013) - Campbell-Page, Ruth M.; Shaw-Ridley, Mary
This article describes two ethical dilemmas encountered by our research team during a project working with undocumented immigrants in Toronto, Canada. This article aims to be transparent about the problems the research team faced, the processes by which we sought to understand these problems, how solutions were found, and how the ethical dilemmas were resolved. Undocumented immigrants are a vulnerable community of individuals residing in a country without legal citizenship, immigration, or refugee status. There are more than half a million undocumented immigrants in Canada. Through an academic–community partnership, a study was conducted to understand the experiences of undocumented immigrants seeking health care in Toronto. The lessons outlined in this article may assist others in overcoming challenges and ethical dilemmas encountered while doing research with vulnerable communities.